FEATURES OF FREE RADICAL OXIDATION AND ANTIOXIDANT PROTECTION IN CHILDREN WITH SUGAR DIABETES OF THE FIRST TYPE - I. M. Bykov; L. G. Ivchenko; D. A. Domenyuk; N. Yu. Kostyukova; A. P. Storozhuk; D. M. Ilijev (Кубанский научный медицинский вестник, 2017)
Aim. Assessment of the state of lipid peroxidation, antioxidant defense and oxidative stress indicators on the model of functional activity of neutrophil granulocytes of blood in children with type 1 diabetes mellitus depending on the stage of endocrinopathy compensation.Materials and methods. The material of laboratory-diagnostic and clinical studies was the results of a survey of 38 children without endocrine pathology and 89 children with type 1 diabetes mellitus at various stages of disease compensation. The state of antioxidant protection was assessed taking into account the overall antioxidant activity, superoxide dismutase activity, retinol level, α-tocopherol, the content of reduced and oxidized glutathione. The intensity of lipoperoxidation processes was studied by the level of substrates with conjugated double bonds, diene conjugates, ketodienes, conjugated trienes, malonic dialdehyde, common lipids. Functional activity of neutrophil granulocytes was investigated by means of luminol-dependent chemiluminescence.Results. In children with type 1 diabetes mellitus, the intensification of lipid peroxidation processes and the activation of the antioxidant defense system, including variously directed changes in non-enzymatic mechanisms, are noted against the negative effect of active oxygen species. In children with decompensated type 1 diabetes mellitus, severe lipid metabolism disorders combined with oxidative stress indices increase the course of endocrine pathology, significantly increasing the likelihood of intravascular complications.Conclusion. The coordinated generation of active forms of oxygen and the processes of oxygen-dependent metabolism of blood cells in children with compensated type 1 diabetes mellitus indicates the development of the second stage (resistance) of oxidative stress. Reduction of reactive oxygen species production, reduced activation rate оxygendependent metabolism phagocytes incompleteness phagocytosis mechanisms, correlating with an increase in lesion area (destruction of insulin-producing β-cells) of the pancreas in children with decompensated type 1 diabetes, indicating the occurrence of the third step (debilitation) oxidative stress. Violations of metabolic pathways in children with type 1 diabetes are determined by the intensity of «respiratory burst» of neutrophil granulocytes in the «Lipid peroxidation – antioxidant protection».